Respuesta :
Answer:
x = 6/5
Step-by-step explanation:
Solve for x:
0 = (-5 (x - 6/5))/4
Hint: | Put the fractions in x - 6/5 over a common denominator.
Put each term in x - 6/5 over the common denominator 5: x - 6/5 = (5 x)/5 - 6/5:
0 = (-5)/4 (5 x)/5 - 6/5
Hint: | Combine (5 x)/5 - 6/5 into a single fraction.
(5 x)/5 - 6/5 = (5 x - 6)/5:
0 = (-5)/4 (5 x - 6)/5
Hint: | In (-5 (5 x - 6))/(5×4), divide -5 in the numerator by 5 in the denominator.
(-5)/5 = (5 (-1))/5 = -1:
0 = (-1 (5 x - 6))/4
Hint: | Reverse the equality in 0 = (-(5 x - 6))/4 in order to isolate x to the left hand side.
0 = (-(5 x - 6))/4 is equivalent to (-(5 x - 6))/4 = 0:
(-(5 x - 6))/4 = 0
Hint: | Multiply both sides by a constant to simplify the equation.
Multiply both sides of (-(5 x - 6))/4 = 0 by -4:
(-4 (-(5 x - 6)))/4 = -4×0
Hint: | In (-4 (-(5 x - 6)))/4, divide -4 in the numerator by 4 in the denominator.
(-4)/4 = (4 (-1))/4 = -1:
--1 (5 x - 6) = -4×0
Hint: | Multiply all instances of -1 in -(-(5 x - 6)).
(-1)^2 = 1:
5 x - 6 = -4×0
Hint: | Any number times zero is zero.
0 (-4) = 0:
5 x - 6 = 0
Hint: | Isolate terms with x to the left hand side.
Add 6 to both sides:
5 x + (6 - 6) = 6
Hint: | Look for the difference of two identical terms.
6 - 6 = 0:
5 x = 6
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of 5 x = 6 by 5:
(5 x)/5 = 6/5
Hint: | Any nonzero number divided by itself is one.
5/5 = 1:
Answer: x = 6/5